Eritroderma Diduga Akibat Reaksi Obat Allopurinol: Laporan Kasus: Laporan Kasus - Emeralda, Pradissa Avia; Savitri, Dwiana (Cermin Dunia Kedokteran, 2025)
Introduction: Erythroderma is a condition of generalized erythema and scaling of the skin. It has been associated with DRESS (drug reaction with eosinophilia and systemic symptoms) syndrome and is potentially life-threatening. Case: A 55-year-old female with generalized erythema, pruritus, malaise, and edema of her face for 7 days. She had a history of type 2 diabetes mellitus and was in oral allopurinol treatment for the last 2 weeks. Extensive generalized erythematous plaques and hyperkeratotic scales were observed on the face, neck, chest, arms, legs, back, and glutea. Laboratory workup revealed eosinophilia, mild hypoalbuminemia, hyperglycemia, and elevated liver enzyme level. Discussion: Erythroderma is an emergency case in dermatovenereology and needs hospitalization. A patient with drug-induced erythroderma with internal organ involvement has been associated with DRESS syndrome and needs further observation of cardiac, liver, and kidney status. Conclusion: Allopurinol is a potential trigger for erythroderma. Drug-induced erythroderma is closely related to DRESS syndrome. Allopurinol use requires caution to avoid complications and prevent recurrence.